PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI KOMPUTER OLEH PEGAWAI DAN KERJASAMA TIM TERHADAP KINERJA PEGAWAI - Iin Verawati Marbun; Saut Purba; Erwin Pardede (JURNAL PROINTEGRITA, 2019)
This research was conducted to find out how the influence of the Use of Computer Information Technology by Employees and Team Cooperation on Employee Performance (Case Study at the Medan Academy of Engineering and Aviation Safety Office). This research was carried out on Employees of the Medan Aviation Engineering and Safety Office. Type of quantitative research. The population in the study were 89 people and 30% were made into a sample, namely 30 employees of the ASN in the Central Land Transportation Management Office of Medan I I Region of the Ministry of Transportation, having their address at Jalan Persatuan No. 5 Medan. Test the validity of the data using validity, reliability. Analysis prerequisite test uses multicollinearity test, heteroscedasticity test, normality test, and linearity test. Data analysis techniques using simple regression test and multiple regression Calculation using SPSS for Windows. The results of a single regression analysis show that (1) The Use of Computer Information Technology by Employees has a positive and significant effect on the performance of the Medan Academy of Engineering and Aviation Safety Employees with a t test value of 10.469 (2) Team Cooperation has a positive and significant effect on the performance of Technical Academic Office Staff and Medan Aviation Safety amounting to (3) The results of multiple regression analysis indicate that the use of computer information technology by employees and teamwork simultaneously has a positive and significant effect on the performance of the Medan Academy of Engineering and Aviation Safety Employees with a calculated F value of 189,039 and a coefficient of determination equal to 81%. It was concluded that the use of computer information technology by employees and team collaboration had a positive and significant effect on the performance of Medan Academy of Engineering and Aviation Safety Employees.